Early re-do surgery for glioblastoma is a feasible and safe strategy to achieve complete resection of enhancing tumor. - Philippe Schucht (Public Library of Science (PLoS), 2013)
Background Complete resection of enhancing tumor as assessed by early (<72 hours) postoperative MRI is regarded as the optimal result in glioblastoma surgery. As yet, there is no consensus on standard procedure if post-operative imaging reveals unintended tumor remnants. Objective The current study evaluated the feasibility and safety of an early re-do surgery aimed at completing resections with the aid of 5-ALA fluorescence and neuronavigation after detection of enhancing tumor remnants on post-operative MRI. Methods From October 2008 to October 2012 a single center institutional protocol offered a second surgery within one week to patients with unintentional incomplete glioblastoma resection. We report on the feasibility of the use 5-ALA fluorescence guidance, the extent of resection (EOR) rates and complications of early re-do surgery. Results Nine of 151 patients (6%) with glioblastoma resections had an unintentional tumor remnant with a volume >0.175 cm(3). 5-ALA guided re-do surgery completed the resection (CRET) in all patients without causing neurological deficits, infections or other complications. Patients who underwent a re-do surgery remained hospitalized between surgeries, resulting in a mean length of hospital stay of 11 days (range 7-15), compared to 9 days for single surgery (range 3-23; p=0.147). Conclusion Our early re-do protocol led to complete resection of all enhancing tumor in all cases without any new neurological deficits and thus provides a similar oncological result as intraoperative MRI (iMRI). The repeated use of 5-ALA induced fluorescence, used for identification of small remnants, remains highly sensitive and specific in the setting of re-do surgery. Early re-do surgery is a feasible and safe strategy to complete unintended subtotal resections.